(untitled) (Al-Aasar, 2025)
Huzoor Dhiya al-Umma Pir Muhammad Karam Shah Al-Azhari (رحمت اللہ علیہ) is regarded as one of the great personalities of the Indian subcontinent who introduced the Muslim Ummah to the Quran, Hadith, and the Seerah of Prophet Muhammad (صلى الله عليه وسلم). Through his continuous efforts, he enlightened millions of misguided individuals about the teachings of Islamic Sharia. With his writings, various lectures, and spiritual blessings, he illuminated people’s hearts with the light of guidance. He was a beacon of light for those who had lost their way. Pir Karam Shah Al-Azhari (رحمت اللہ علیہ) was a personification of the exemplary character of the Prophet Muhammad (صلى الله عليه وسلم), and his personality encompassed all virtues. He authored a five-volume Tafseer called Dhiya al-Quran, in which he introduced each Surah before discussing it. This introduction includes the occasion of revelation, the number of verses, the divisions (Ruku’at) of the Surah, and a summary of its content. This allows the reader to gain a complete understanding of each Surah. This article discusses the topics related to the Sciences of the Quran as presented in the Tafseer Dhiya al-Quran.